Linguistik und Medizin Sprachwissenschaftliche Zugänge und interdisziplinäre Perspektiven - Iakushevich, Marina; Ilg, Yvonne; Schnedermann, Theresa (Sprache und Wissen (SuW), 2021)
Linguistics and medicine is a growing branch of research in the medical humanities. The interdisciplinary contributions in this volume address current, socially relevant issues in doctor-patient communication, public mass-media discourses, and specialist communication. They examine the processes through which knowledge is constituted, negotiated, and transferred in various sociocultural contexts.